2015
DOI: 10.2217/imt.14.115
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for Food Allergies: A Myth or a Reality?

Abstract: Food allergy is a worldwide issue, with an estimated prevalence of 2-10%. An effective treatment is not available for people affected and the only management is the avoidance of the allergen. Oral immunotherapy and sublingual immunotherapy have been tested by several authors, in particular for milk, egg and peanuts allergy, with significant results in term of desensitization induction. The achievement of tolerance is by the contrary doubtful, with different results obtained. In this review, we reviewed protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 70 publications
0
34
0
Order By: Relevance
“…Numerous single-center studies have been published; although they have demonstrated induction of varying degrees of desensitization, there is concern about significant risk of severe treatment-associated adverse reactions . Moreover, only a minority of treated patients achieve any measure of longer-term tolerance …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous single-center studies have been published; although they have demonstrated induction of varying degrees of desensitization, there is concern about significant risk of severe treatment-associated adverse reactions . Moreover, only a minority of treated patients achieve any measure of longer-term tolerance …”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, only a minority of treated patients achieve any measure of longerterm tolerance. 8,9 Epicutaneous immunotherapy uses an allergenadsorbed patch (peanut patch), which in murine models has been shown to deliver allergen to the epidermal layer of normal intact skin, where it is taken up by Langerhans cells and transported to regional lymph nodes. 10 After a recent phase 1 trial in peanut-allergic individuals demonstrated safety and tolerability, 11 a 1-year phase 2b trial of the peanut patch was conducted in peanut-allergic patients to identify the most effective dose and to establish its adverse event (AE) profile, efficacy, and acceptability.…”
mentioning
confidence: 99%
“…In addition to this theory of hydrocephalus formation, defined as "classical," Greitz has proposed a new theory on the dynamics of CSF and on the development of hydrocephalus as a disorder of intracranial pulsations, [19][20][21] according to which the reabsorption of CSF occurs through the vessels capillaries (hemodynamic theory): in this sense, communicating hydrocephalus would be linked to any cause that narrows the intracranial arteries while obstructive hydrocephalus from a compression of the cortical veins. The onset of symptoms, in both cases, would be determined by the reduction of oxygenated blood directed to the brain parenchyma.…”
Section: Physiopathologymentioning
confidence: 99%
“…1). [22][23][24] In cases of secondary microcephaly, the OFC is normal at birth but decreases postnatally, becoming apparent within the first year of life. Unlike the primary type, this form of microcephaly is frequently associated with common progressive motor and cognitive impairments.…”
Section: Etiologymentioning
confidence: 99%